The sensitivity of direct faecal examination, faecal flotation and centrifugal sedimentation / flotation in the diagnosis of canine spirocercosis - Van der Merwe, Liesel Laura (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2011.